Wśród uchodźców na Węgrzech i w podziemiu w kraju. Wojenne losy ppłk. Wacława Lipińskiego (1939-1945) - Pietrzak, Jacek (Acta Universitatis Lodziensis. Folia Historica, 1997)
Colonel Wacław Lipiński (1896-1949) was a veteran of the World War I (in J. Piłsudski’s Ist Brigade of Polish Legions), a regular army officer, a historian and a publicist. He was one of the best popularizers of Polish modem history, however he was often criticized for creating Piłsudski’s legend. In September 1939 Lipiński, as a chief of propagand, became a hero of the defence of Warsaw. At the beginning of the occupation he went to Hungary to avoid his expected arrest by Gestapo. He was active there as a publicist and lecturer. In 1942 Lipiński returned Poland and became a leader of Konwent Organizacji Niepodległościowych - KON (The Assembly of the Organizations for the Independence of Poland). It was one of small but active groups of the Resistance, created by former members of Pilsudski’s political camp - sanacja. KON opposed strongly Polish Government in exile. Lipiński criticized its dependence on Great Britain, a compromise with USSR (Sikorski-Majski Treaty, 1941) and a withdrawal of Piłsudski-ites from an influence on politics and army. He warned also against Soviet domination over post-war Poland and opposed an anti-German insurrection. Lipiński presented his opinions in brochures and articles published in conspiracy as well as in memorials for political and military authorities. Although sanacja underground groups had a little influence on the political Resistance, Lipiński expressed one of the most controversial conceptions of Polish political thinking during the World War II. After the war Lipiński took part in the anti-communist underground movement. In December 1947 he was sentenced to the death penalty during the world-famous trial of the leaders of the underground opposition. Although the sentence was officially changed, Lipiński was probably murdered in a prison in 1949.